An Evaluation of Panel Nonresponse and Linkage Consent Bias in a Survey of Employees in Germany. (25th October 2015) - Sakshaug, Joseph W.; Huber, Martina
Abstract: Surveys are susceptible to multiple error sources that threaten the validity of inferences drawn from them. While much of the survey methods literature has focused on identifying errors in cross-sectional surveys, errors in panel surveys have received less attention. Administrative records linked to the entire sample (respondents and nonrespondents) can be useful for studying various errors in panel surveys, including nonresponse, which tends to accumulate over multiple waves of the study. Record data can also be used to study errors due to linkage consent, which is commonly requested in panel surveys but not provided by all respondents. In this paper, we present bias estimates for both error sources from a panel survey in Germany. The bias estimates are derived from administrative data collected on a sample of employees who were invited to participate in the panel. We find evidence of increasing nonresponse bias over time for cross-sectional and longitudinal outcomes. The opposite pattern is observed for linkage consent bias, which decreases over time when respondents who do not provide consent in a prior wave are asked to reconsider their decision in subsequent waves. We conclude with a discussion of the practical implications of these findings and propose suggestions for future research.